EFL Students’ Self-Regulation in Online Learning during the Covid-19 Pandemic - Krismalita Sekar Diasti; Heny Hartono (PANYONARA: Journal of English Education, 2023)
This study investigates self-regulation in online learning during the Covid-19 pandemic, specifically how students regulate their learning activities amidst challenging circumstances. This research focuses on the challenges faced by students in online learning and the strategies students employed to regulate their learning process. The participants of this study were 38 students from two private universities in Indonesia. Data were collected through FGD and analyzed by using open coding. The results of this study revealed that students dealt with difficulties during online learning, specifically related to an internet connection, an unsupportive learning environment, and negative emotions. However, they utilized self-regulated learning strategies to support them in online learning activities such as self-consequating, environmental structuring, emotion regulation, and time management.